Legal implications of mixed marriage without a prenuptial agreement on land ownership: Case study of Supreme Court Decision Number. 539 K/AG/2021 - Hartanto, Stefanie; Susilo, Mohammad Ahmad Eko (Jurnal Civics: Media Kajian Kewarganegaraan, 2025)
Mixed marriages between Indonesian citizens and foreign nationals raise complex legal issues, particularly regarding land ownership rights in Indonesia. The absence of a prenuptial agreement in such marriages can result in the loss of land ownership rights for the Indonesian spouse, as regulated under the Marriage Law and the Basic Agrarian Law. The Supreme Court Decision No. 539 K/AG/2021 serves as a significant case to examine the legal implications of mixed marriages without a prenuptial agreement, and this study aims to analyse its impact on the protection of land ownership rights for Indonesian citizens. This research applies a normative juridical qualitative approach by analysing legislation, legal doctrines, and court decisions related to mixed marriages and land ownership. The primary legal basis includes the Marriage Law, the Basic Agrarian Law, Constitutional Court Decision No. 69/PUU-XIII/2015, and Supreme Court Decision No. 539 K/Ag/2021, supported by secondary sources such as journals and legal literature. Through descriptive-analytical analysis, this study highlights the legal considerations and implications of the absence of a prenuptial agreement in mixed marriages, particularly regarding the protection of land ownership rights. The research results show that Supreme Court Decision No. 539 K/Ag/2021 emphasises fairness and legal certainty by recognising land and property acquired during mixed marriages without a prenuptial agreement as joint property to be divided equitably. The decision also highlights potential legal risks, as it indirectly enables foreign nationals to benefit from land ownership rights that are prohibited under the Basic Agrarian Law. Therefore, a prenuptial agreement is an essential preventive measure to provide legal clarity, protect Indonesian citizens, and avoid future legal complications in mixed marriages.